Efektivitas Eksekusi Jaminan Hak Tanggungan pada Pembiayaan Bermasalah di Bank Tabungan Negara Kantor Cabang Syariah Solo - Dani Dwi Meylawati; Andy Putra Wijaya; Riduwan Riduwan; Mufti Alam Adha (Prodi Hukum Ekonomi Syariah Fakultas Agama Islam, Universitas Muhammadiyah Purwokerto, 2024)
Financial institutions, including the branch office of BTN Syariah in Solo City, often face non-performing financing. One strategy the branch office of BTN Syariah in Solo City uses to resolve non-performing financing is to execute the mortgage guarantee, which is carried out as the last alternative. This research aims to determine the effectiveness of strategies to overcome obstacles in implementing the execution of the mortgage guarantee for non-performing financing at the branch office of BTN Syariah in Solo City. This field research uses a descriptive qualitative approach. The object of this research is the branch office of BTN Syariah in Solo City. The primary and secondary data sources are collected through observation, interviews, documentation, and triangulation. The results state that the execution of the mortgage guarantee on non-performing financing at the branch office of BTN Syariah in Solo City has yet to be said to be effective. The strategy to overcome obstacles in implementing the execution of mortgage guarantees carried out by the branch office of BTN Syariah in Solo City is visiting a notary and attempting to rescue the non-performing financing, continuing to sell the collateral until it is sold with no period, and trying to cooperate and ensuring that the steps in the execution process are under legal provisions. Meanwhile, the strategy to overcome obstacles carried out by the State Property and Auction Services Office (KPKNL) is proposing additional auction officials to maximize services. In addition, KPKNL is collaborating with various parties to organize outreach regarding the procedures for bidding for auctions and updating regulations related to auctions.